2016
DOI: 10.5296/jas.v4i3.9955
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Seed Hardening Techniques on Vigor, Growth and Yield of Wheat under Drought Conditions

Abstract: Exploring ways to improve stand establishment and crop productivity under abiotic stresses like drought is important. Two years experiments were conducted at University of Agriculture, Peshawar-Pakistan to examine the efficacy of six pre-sowing seed hardening agents. Seeds of wheat cultivar Uqab-2000 were hardened in six different chemicals of various concentration viz; PEG-8000 (10%), CaCl 2 (4%), KNO 3 , (3%), Mannital (4%), NaCl (5%), Na 2 SO 4 (2%) along with water soaking and dry seeds as control for 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
3
4
0
Order By: Relevance
“…The findings further support the earlier work on wheat (Triticum aestivum) (Amin et al 2016) and rice (Oryza sativa) (Lee, Kim 2000), where an improved germination rate and percentage in seeds subjected to seed invigoration for 24 hours were reported. Seed invigoration with other osmotic solutions, such as seed priming with GA3, osmoconditioning with PEG-6000 (Dursan, Ekinci 2010) and hydropriming with distilled water for 24 hours, significantly reduced the germination time and improved the emergence rate and seedling vigour.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The findings further support the earlier work on wheat (Triticum aestivum) (Amin et al 2016) and rice (Oryza sativa) (Lee, Kim 2000), where an improved germination rate and percentage in seeds subjected to seed invigoration for 24 hours were reported. Seed invigoration with other osmotic solutions, such as seed priming with GA3, osmoconditioning with PEG-6000 (Dursan, Ekinci 2010) and hydropriming with distilled water for 24 hours, significantly reduced the germination time and improved the emergence rate and seedling vigour.…”
Section: Resultssupporting
confidence: 91%
“…The germination of onion seeds, for example, especially under stressful conditions, such as low temperatures, continues to be a matter of significant importance to growers who plant the seed directly in the field. Seed enhancement through invigoration or priming has resulted in a significant improvement in the farmers' ability to achieve this goal both in an open and controlled environment (Amin et al 2016). Seed invigoration is a pre-sowing, controlled-hydration environment in which seeds are exposed to an external water potential that is sufficiently low enough to prevent radicle protrusion, but is able to stimulate physiological and biochemical activities (Adetunji et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Bread wheat seeds sourced from formal and intermediary seed systems produced the highest SL compared to seeds sourced from farmers. Khan et al [ 22 ] reported that the longest SL (17.5 cm) was obtained from seeds sourced from (formal) compared to farmer-saved seed (15.6 cm) which supports our current study results. Similarly, a report by Ref.…”
Section: Resultssupporting
confidence: 91%
“…Similar results that supported current study reported by Refs. [ 16 , 22 ] indicated that wheat seed sources had a significant effect on TKW. In addition, rice seed sources had a significant difference in 1000-grain weights [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…During the pre-sowing period (July to September), only a meager 10.4 mm of precipitation accumulated in the 2019 GS, in stark contrast to the more than 70 mm recorded in the same period for the 2020 GS (Table 1). Considering that the average for this period, as indicated by the 30-year time series in Table 1, slightly exceeds the 27 mm accumulated, the contrasting precipitation levels-below-average in 2019 and well above-average in 2020-inevitably resulted in a significantly lower germination capacity and initial growth (Amin et al 2016;Grahmann et al 2021) of FA seeds in the 2019 GS compared to those in the 2020…”
Section: Discussionmentioning
confidence: 92%